(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the psychological impact of social networks on personality development. The positive (socialization, self-expression, information acquisition) and negative (social comparison, dependence, cyberbullying) aspects of social networks are covered based on a scientific approach. Also, the characteristics of the impact during adolescence and preventive recommendations are presented. Keywords: socialization, website, concept, content, psychological impact